Association between insulin resistance and cancer among patients of the diagnostic Nuclear Imaging Center at UPM and Hospital Serdang - Korie, Ezinne Oyidia (2013)
Insulin resistance (IR) is a major risk factor for Type 2 diabetes. Type 2 diabetes among other non-communicable diseases are major public health concerns with increased significance and prevalence. Cancer on the other hand was a leading cause of death worldwide in 2008. Studies have attributed the link between carcinogenesis and insulin resistance to hyperinsulinemia. The Hyperinsulinemia Theory proposes that high levels of insulin decreases the production of insulin growth factor 1 (IGF-1) binding proteins and hence increases the levels of free IGF-1. The bioactivity of free IGF-1 has been known to increase tumor turnover rate. The main objective of this study is to determine the association between insulin resistance and cancer among patients at the Diagnostic Nuclear Imaging in University Putra Malaysia and Hospital Serdang, Malaysia. This study hypothesized significant association between insulin resistance and cancer. This case-control study was carried out at the Diagnostic Nuclear Imaging Center at the Medical Faculty in UPM (Universiti Putra Malaysia) and the surgical ward of Hospital Serdang. Based on the sample size calculation, it involved a total sample size of 100 (age and sex matched 45 cases and 55 controls). Consecutive sampling was used for patient recruitment. Insulin resistance was determined by the Homeostasis Model assessment of Insulin resistance (HOMA-IR) which is a validated index of insulin resistance. It correlates strongly and inversely with the basic Insulin Sensitivity Clamp Index; derived from the hyperinsulinemic euglycemic clamp (r = -0.572, P<0.001) and also a more practical method of measuring insulin resistance in large epidemiological studies. HOMA-IR, metabolic parameters and anthropometric measurements were collected and determined in all subjects. From the results, using logistic regression, insulin resistance was independently associated with cancer (Adjusted OR= 12.25. 95% CI = 3.20, 46.83) There was also significant association between obesity and cancer (Adjusted OR=3.33, 95% CI = 1.08, 10.31). The presence of IR in cancer cases if researched further might have the ability to show insights on the role of insulin resistance on cancer in general and also cancer prevention and treatment.